2014
DOI: 10.1088/1367-2630/16/11/113035
|View full text |Cite
|
Sign up to set email alerts
|

Quantum size effects in chemicurrent measurements during low-temperature oxidation of Mg(0001) epilayers

Abstract: The reactivity of Mg epilayers on Si(111)-7 × 7 towards molecular oxygen is investigated as a function of the metal film thickness in the range between 7 and 45 monolayers. Quantum well and surface states are characterized with ultraviolet photoelectron spectroscopy demonstrating the epitaxial and single-crystalline structure of the Mg films. The oxidation rate is monitored during the reaction by measuring chemicurrents at 110 K in the Mg/p-Si(111) Schottky diodes due to the non-adiabatic character of at least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…Third, photoelectron spectroscopy on Ag/Au(111) revealed additional quantum well electronic states (QWS) between thicknesses of 7 and 40 ML. , The energetic position and density of such states are strongly affected by the film thickness. We also note that an effect of QWS on the magnitude of chemicurrents was reported in a prior study . In our work, we observe no change in vibrational relaxation probability in this thickness range.…”
Section: Discussionsupporting
confidence: 83%
“…Third, photoelectron spectroscopy on Ag/Au(111) revealed additional quantum well electronic states (QWS) between thicknesses of 7 and 40 ML. , The energetic position and density of such states are strongly affected by the film thickness. We also note that an effect of QWS on the magnitude of chemicurrents was reported in a prior study . In our work, we observe no change in vibrational relaxation probability in this thickness range.…”
Section: Discussionsupporting
confidence: 83%
“…During the deposition of Mg onto Mg/p-Si(001), chemically induced current (referred to as chemicurrent) was measured and found to be exponentially attenuated with increasing Mg film thickness. 14 The attenuation length was found to be 5 nm, a typical value for hot electron transport in metal films. Upon further investigation of this system, the reactivity of the Mg film with molecular oxygen was characterized.…”
Section: Introductionmentioning
confidence: 97%
“…The attenuation length was found to be 5 nm, a typical value for hot electron transport in metal films. Upon further investigation of this system, the reactivity of the Mg film with molecular oxygen was characterized . This reactivity was found to be a function of the Mg film thickness, with chemicurrent resulting from Mg oxidation exhibiting a maximum for Mg film thickness of 9 and 13 monolayers.…”
Section: Introductionmentioning
confidence: 99%
“…Nanostructure morphology plays a crucial role on the generation of reaction current, as was evident through the Hagemann et al communiqué on Mg/p-Si(111) systems under exposure to O 2 . They found that the reaction current generated is strongly dependent upon film thickness; for thicknesses ∼ 10 monolayers, the reaction current is more than double relative to that generated by thicker films (up to 45 monolayers).…”
Section: Introductionmentioning
confidence: 91%